Freshwater fish diversity hotspots for conservation priorities in the Amazon Basin. Issue 4 (23rd March 2020) - Jézéquel, Céline; Tedesco, Pablo A.; Darwall, William; Dias, Murilo S.; Frederico, Renata G.; Hidalgo, Max; Hugueny, Bernard; Maldonado‐Ocampo, Javier; Martens, Koen; Ortega, Hernan; Torrente‐Vilara, Gislene; Zuanon, Jansen; et al.
Abstract: Conserving freshwater habitats and their biodiversity in the Amazon Basin is a growing challenge in the face of rapid anthropogenic changes. We used the most comprehensive fish‐occurrence database available (2355 valid species; 21, 248 sampling points) and 3 ecological criteria (irreplaceability, representativeness, and vulnerability) to identify biodiversity hotspots based on 6 conservation templates (3 proactive, 1 reactive, 1 representative, and 1 balanced) to provide a set of alternative planning solutions for freshwater fish protection in the Amazon Basin. We identified empirically for each template the 17% of sub‐basins that should be conserved and performed a prioritization analysis by identifying current and future (2050) threats (i.e., degree of deforestation and habitat fragmentation by dams). Two of our 3 proactive templates had around 65% of their surface covered by protected areas; high levels of irreplaceability (60% of endemics) and representativeness (71% of the Amazonian fish fauna); and low current and future vulnerability. These 2 templates, then, seemed more robust for conservation prioritization. The future of the selected sub‐basins in these 2 proactive templates is not immediately threatened by human activities, and these sub‐basins host the largest part of Amazonian biodiversity. They could easily be conserved if no additional threats occur between now and 2050. Abstract : Article Impact Statement : Alternative scenarios of diversity hotspots for freshwater fish can be used to define conservation priorities in the Amazon Basin. Abstract : Puntos Calientes de Diversidad de Peces de Agua Dulce para las Prioridades de Conservación en la Cuenca del Amazonas Resumen: Cada día, la conservación de los hábitats de agua dulce y su biodiversidad en la cuenca del Amazonas es un reto creciente de cara a los rápidos cambios antropogénicos. Usamos la base de datos de presencia de peces más completa que existe (2, 355 especies válidas; 21, 248 puntos de muestreo) y tres criterios ecológicos (carácter irremplazable, representatividad y vulnerabilidad) para identificar los puntos calientes de biodiversidad con base en seis patrones de conservación (tres proactivos, uno reactivo, uno representativo y uno balanceado) y así proporcionar un conjunto de soluciones alternativas para la planeación de la protección de peces de agua dulce en la cuenca del Amazonas. Identificamos para cada patrón de manera empírica el 17% de las subcuencas que deberían conservarse y realizamos un análisis de priorización identificando amenazas actuales y a futuro (2050) (es decir, grado de deforestación y fragmentación del hábitat causado por presas). Dos de nuestros tres patrones proactivos tuvieron alrededor del 65% de su superficie cubierta por áreas protegidas; niveles altos de carácter irremplazable (60% de especies endémicas) y de representatividad (71% de la fauna ictiológica del Amazonas); y una vulnerabilidad baja actual y a futuro. Entonces, estos dos patrones parecen estar más completos para la priorización de la conservación. El futuro de las subcuencas en estos dos patrones proactivos no está amenazado por las actividades humanas a corto plazo. Además, estas subcuencas albergan la mayor parte de la biodiversidad amazónica. Se podrían conservar fácilmente si ninguna amenaza adicional sucede entre ahora y el 2050.